2011
DOI: 10.1016/j.ejcts.2011.02.035
|View full text |Cite
|
Sign up to set email alerts
|

A new pulmonary valve cusp plasty technique markedly decreases transannular patch rate and improves midterm outcomes of tetralogy of Fallot repair

Abstract: Excellent outcome can be achieved even with 95% freedom of TAP in complete repair of tetralogy. The function of most patients' pulmonary valve was well preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Postoperative ischaemic electric signs without any acute coronary syndrome during the hospital stay significantly increase the risk of long-term heart failure (OR = 26). The postoperative RV/LV pressure ratio is also directly linked to the quality of the surgical repair [21,22]. We demonstrated that an immediate postoperative RV/LV pressure ratio >0.5 was independently associated with a long-term RV/LV pressure ratio >0.5, but was not a risk factor for reoperation or mortality.…”
Section: Discussionmentioning
confidence: 75%
“…Postoperative ischaemic electric signs without any acute coronary syndrome during the hospital stay significantly increase the risk of long-term heart failure (OR = 26). The postoperative RV/LV pressure ratio is also directly linked to the quality of the surgical repair [21,22]. We demonstrated that an immediate postoperative RV/LV pressure ratio >0.5 was independently associated with a long-term RV/LV pressure ratio >0.5, but was not a risk factor for reoperation or mortality.…”
Section: Discussionmentioning
confidence: 75%
“…[2] The pulmonary valve morphology in patients with TOF is commonly abnormal, and most data in literature has been obtained from the study of surgical heart specimens during autopsy, which could be biased due to different survival rates of patients with various anatomic variations. Because of the current trends towards valve sparing techniques and native valve cusp augmentation techniques to reduce the incidence of pulmonary regurgitation and its long-term complications following corrective TOF repair,[34] preoperative awareness of pulmonary valve morphology could contribute towards better surgical planning. Multidetector cardiac computed tomography (CT) gives good anatomic detail of the cardia, its vascular structures, and valves.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, transannular patches were intentionally downsized and reconstructed to result in right ventricular gradients of approximately 20 mm Hg. 11,12 More comprehensive valve-sparing techniques that included a supravalvar pantaloon autologous pericardial patch for supravalvar pulmonary stenosis were highlighted by several authors. [8][9][10] These techniques permitted an increased incidence of pulmonary valve preservation during initial repair in up to 70% of patients 8 compared with 40% or less in other reports.…”
mentioning
confidence: 99%